Sequential synthesis of free-standing high quality bilayer graphene from recycled nickel foil. (January 2016) - Seah, Choon-Ming; Vigolo, Brigitte; Chai, Siang-Piao; Ichikawa, Satoshi; Gleize, Jérôme; Le Normand, François; Aweke, Fitsum; Mohamed, Abdul Rahman
Abstract: The recycle and reuse of catalyst is an active research area motivated by the reduction of graphene production cost. Our process is derived from the conventional CVD method widely utilized for graphene synthesis. It allows the formation of uniform bilayer graphene by limiting the segregation of carbon. The relatively thick foil of Ni used as catalyst plays a crucial role in solubilizing and trapping large amount of carbon adatoms. The trapping mechanism is enhanced by the high-speed cooling subsequent to the growth stage. Segregation of carbon is then efficiently quenched and uniform bilayer graphene could be prepared. The separation process is also optimized thanks to a protective effect from the nickel carbide (Ni3 C) formed. We show that Ni3 C minimizes the catalyst lost due to the separation of graphene and it also facilitates the graphene separation process. The Ni foil could be recycled up to 6 times without significant variation in number of layers and perfectness in crystallinity of the obtained bilayer graphene. Besides, we discuss of the role playing by the roughness of the catalyst surface for bilayer graphene separation in our process.